Digital employee experience as a strategic driver of engagement and performance: Evidence from the airline industry - Awaldi, Awaldi; Raharjo, Kusdi; Noerman, Teuku; Ruhana, Ika (Edelweiss Applied Science and Technology, 2026)
In the era of digital transformation, employees’ digital experiences have become a critical determinant of organizational success; however, empirical research examining digital employee experience as a strategic resource driving engagement and performance remains limited, particularly in high-pressure service sectors such as the airline industry. Grounded in Social Cognitive Theory (SCT) and the Job Demands–Resources (JD–R) model, this study investigates the effects of digital employee experience and organizational culture on employee well-being and engagement, and subsequently on employee performance. Using a quantitative approach, data were collected from 308 employees of a national flag carrier airline operating in Indonesia across multiple directorates and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The structural model was specified as a Type I (reflective–reflective) higher-order construct (HOC) to capture construct multidimensionality. The findings reveal that digital employee experience and organizational culture significantly enhance employee well-being, which subsequently improves employee performance. However, digital employee experience does not significantly affect employee engagement, whereas organizational culture exerts a significant positive effect on engagement. Both well-being and engagement partially mediate these relationships, highlighting their pivotal roles.